Special educational needs/disabilities and the evolution of the primary school Special Educational Needs Coordinator (SENCO) in England - Smith, Andrew (Journal of Exceptional People, 2020)
This review paper presents the evolving role of the Special Educational Needs Coordinator (SENCO) in mainstream primary schools set within the changing political/ideo logical National Educational landscape in England.
Keywords: United Kingdom; příprava učitelů; dítě; vytváření politiky; vzdělávací modely; vzdělávací politika; integrovaná výuka; institucionální management; lidé; Spojené království; Models, Educational; speciální vzdělávání; školy; učitelé; Schools; Humans; Education, Special; Child; School Teachers; Mainstreaming, Education; Policy Making; koordinátor speciálního vzdělávání; Institutional Management Teams; Teacher Training